PENGARUH UKURAN PERUSAHAAN, KOMPLEKSITAS PERUSAHAAN, LEVERAGE, FINANCIAL DISTRESS, PROFITABILITAS, DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP PENGUNGKAPAN HAL AUDIT UTAMA (Studi pada Perusahaan Non-Keuangan Terdaftar di Bursa Efek Indonesia Periode 2023-2024) - Muhammad Ahsan Makarim; Darsono Darsono (Diponegoro Journal of Accounting, 2026)
This study examines determinants of Key Audit Matters (KAM) disclosure in non-financial companies with high audit complexity listed on the Indonesia Stock Exchange (IDX) during 2023-2024, representing the initial phase of full implementation of OJK Regulation No. 30 of 2023. Using a quantitative explanatory approach with pooled cross-sectional design, the sample consists of 558 firm-year observations from industrial, basic materials, and consumer non-cyclicals sectors selected through total sampling. The dependent variable is measured by the absolute number of KAM disclosed in independent auditor reports. Data are analysed using Poisson regression with log link function and robust standard errors (HC3) to address underdispersion. Results indicate that firm size (SIZE) and firm complexity (COMP) positively and significantly affect KAM disclosure (p < 0.01), confirming agency theory predictions. Simultaneously, all independent variables significantly influence KAM disclosure (LR χ² = 12.77; p = 0.047). Leverage, financial distress, profitability, and auditor industry specialization show no significant partial effects. These findings suggest that structural firm characteristics particularly scale and operational complexity are the primary determinants of audit risk communication intensity through KAM during the early regulatory implementation phase in Indonesia.